2018
DOI: 10.1364/optica.5.001283
|View full text |Cite
|
Sign up to set email alerts
|

Propagation-enhanced generation of intense high-harmonic continua in the 100-eV spectral region

Abstract: The study of core electron dynamics through nonlinear spectroscopy requires intense isolated attosecond extreme ultraviolet or even X-ray pulses. A robust way to produce these pulses is high-harmonic generation (HHG) in a gas medium. However, the energy upscaling of the process depends on a very demanding next-generation laser technology that provides multi-terawatt (TW) laser pulses with few-optical-cycle duration and controlled electric field. Here, we revisit the HHG process driven by 16-TW sub-two-cycle la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…In real experiments, if HHG works under the usual phase matching conditions, where the ionization is lower than the critical ionization rate (usually less than few percent) [37], the driving laser can be considered unmodified by the gas, and our conclusions are not affected by these effects. However, in the case of high ionization, the shape of the laser beam during propagation will be modified by the electrons in the medium [38][39][40][41], and the far-field shape of the laser beam profile is expected to change relevantly. In such cases, the ionization term must be included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In real experiments, if HHG works under the usual phase matching conditions, where the ionization is lower than the critical ionization rate (usually less than few percent) [37], the driving laser can be considered unmodified by the gas, and our conclusions are not affected by these effects. However, in the case of high ionization, the shape of the laser beam during propagation will be modified by the electrons in the medium [38][39][40][41], and the far-field shape of the laser beam profile is expected to change relevantly. In such cases, the ionization term must be included.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, this method is valid when the nonlinear effect of the medium on the generation beam is not obvious. If the ionization rate is too high, the ionization term must be included in equation 2 [39,41].…”
Section: Theoretical Model For Beam Propagation Simulationmentioning
confidence: 99%
“…In real experiments, if HHG works under the usual phase matching conditions, where the ionization is lower than the critical ionization rate (usually less than a few percent) [71], the driving laser can be considered unmodified by the gas and our conclusions are not affected by these effects. However, in the case of high ionization, the shape of the laser beam during propagation will be modified by the electrons in the medium [33,[72][73][74] and the far-field shape of the laser beam profile is expected to change relevantly. To analyze the effect of ionization of the generation medium, we carried out additional simulations (see Section 3 in Supplementary Material for the details).…”
Section: Generation Beam (Xuv Arm)mentioning
confidence: 99%
“…Similarly, the dipole-induced phase mismatch has a complex spatial dependence through the variation of laser intensity with z (∆k d = α∂I 0 /∂z [46]). At the same time, it can be shown that for a guiding capillary [43], in case of a self-guided beam [21,47], or in experiments where loose focusing geometry is used (expressed as L med ≪ z R in a more quantitative form), this intensity variation is slow and the related phase-mismatch term can be neglected [4]. Also, when only short quantum trajectories are relevant, the proportionality constant α is small, and ∆k d ≈ 0 [4].…”
Section: Phase Matching Terms and Their Pressure Dependence In High-h...mentioning
confidence: 99%